2010
DOI: 10.1007/s10681-010-0250-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential preference of Capsicum spp. cultivars by Aphis gossypii is conferred by variation in volatile semiochemistry

Abstract: The aim of this study was to demonstrate that Capsicum spp. cultivars are differentially preferred by the cotton aphid, Aphis gossypii, and to investigate the role of volatile semiochemicals in conferring differences in host preferences. Two preference assays were conducted in 2008 under greenhouse conditions. Fourteen different commercially available cultivars were grown in cages protected by an anti-aphid net, and were infested 60 days after planting, through the release of ten adult female A. gossypii per p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
3
18
0
2
Order By: Relevance
“…Therefore, the rosemary genetics may explain the observed differences in aphid behaviour. This is consistent with several studies reporting that the repulsion (or attraction) of the aphid differs according to the VOC profile produced by different cultivars (Storer & van Emden, ; Wang et al , ; da Costa et al , ; Schröder et al , ). This evidence is also valid for other pests sensitive to the olfactory environment, such as thrips Frankliniella occidentalis (Pergande), (Thysanoptera: Thripidae) in rosebushes (Gaum et al , ) and the whitefly Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae) in tomatoes or eggplants (Darshanee et al , ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the rosemary genetics may explain the observed differences in aphid behaviour. This is consistent with several studies reporting that the repulsion (or attraction) of the aphid differs according to the VOC profile produced by different cultivars (Storer & van Emden, ; Wang et al , ; da Costa et al , ; Schröder et al , ). This evidence is also valid for other pests sensitive to the olfactory environment, such as thrips Frankliniella occidentalis (Pergande), (Thysanoptera: Thripidae) in rosebushes (Gaum et al , ) and the whitefly Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae) in tomatoes or eggplants (Darshanee et al , ).…”
Section: Discussionsupporting
confidence: 92%
“…In this sense, genetic selection can be an essential lever for optimizing the effectiveness of rosemary and promoting its use by producers. Indeed, VOC production varies quantitatively and qualitatively according to the cultivars (Satyal et al , ), generating a variable olfactory response from aphids (da Costa et al , ; Staudt et al , ; Rajabaskar et al , ; Schröder et al , ). Still, by the same logic, understanding the action modes of companion plants and identifying the molecules involved should help us to select the most successful genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the attraction of apple, hawthorn, and dogwood flies to host fruit volatile blends decreased when non‐host volatile blends were added to the odour source. On the other hand, less information is available concerning the use of host plant volatiles by phytophagous insects to discriminate between host plant cultivars (Khan et al., 1987; Kalinová et al., 2000; da Costa et al., 2011). The post‐hibernating adults of Anthonomus pomorum (L.) prefer certain apple cultivars to others.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled GC-electrophysiology with C. lucasina revealed the presence of other electrophysiologically active compounds for which no discernable difference in levels between uninfested and A. gossypii infested samples could be detected by GC analysis (data not shown). These included 6-methyl-5-hepten-2-one, which has been shown in other studies to be an important host derived semiochemical for A. gossypii (da Costa et al, 2011), while octanal and decanal have been shown to be host derived semiochemicals for A. fabae (Webster et al, 2010). Investigations into the behavioral roles of the EAG active compounds other than those used in behavioral studies, i.e., 6-methyl-5-hepten-2-one, (Z)-4,8-dimethyl-1,3,7-nonatriene, octanal, nonanal, decanal, 3-methylhexane, n-heptane, methylcyclohexane, α-pinene, and an ethylbenzaldehyde isomer (Fig.…”
Section: Controlmentioning
confidence: 99%